1996
DOI: 10.1111/j.1532-5415.1996.tb01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Balance and Strength Training in Older Adults: Intervention Gains and Tai Chi Maintenance

Abstract: Balance training meaningfully improved all balance measures by restoring performance to a level analogous to an individual 3 to 10 years younger: LOB = -2.0 +/- 0.3 (adjusted paired differences, P < .005 ANOVA); SST = 7.0 +/- 1.2 sec; and FBOS = 9.0 +/- 2.0% of foot length (P < .05). Strengthening increased ISOK by 1.1 +/- 0.1 Nm kg-1 (P < .005). There was no interaction between balance and strength training. Significant gains persisted after 6 months of Tai Chi, although there was some decrement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
240
1
12

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(276 citation statements)
references
References 56 publications
16
240
1
12
Order By: Relevance
“…Also, limits of stability were reported to play a significant role in indicating susceptibility to falls (Girardi et al 2001). In the FICSIT study, TCC benefited elderly practitioners by maintaining balance gains following a 3-month balance training course, and established a trend toward further improvement in balance (Wolfson et al 1996). Tsang and Hui-Chan (2003) also confirmed that long-term TCC practitioners achieved greater limits of stability.…”
Section: Discussionmentioning
confidence: 53%
“…Also, limits of stability were reported to play a significant role in indicating susceptibility to falls (Girardi et al 2001). In the FICSIT study, TCC benefited elderly practitioners by maintaining balance gains following a 3-month balance training course, and established a trend toward further improvement in balance (Wolfson et al 1996). Tsang and Hui-Chan (2003) also confirmed that long-term TCC practitioners achieved greater limits of stability.…”
Section: Discussionmentioning
confidence: 53%
“…24,32,33 Furthermore, our balance training program included exercises that closely mimicked reaching in standing tasks, thereby providing muscle activation associated with functional challenge of maintaining balance. 24,[34][35][36] We, therefore, suggest that the improved function during dynamic tasks might be at least partially attributed to enhancements of the muscle properties.…”
Section: Potential Mechanismsmentioning
confidence: 85%
“…An early RCT by Wolfson et al [25] examined the impact of Tai Chi on maintenance of improvements achieved by healthy older adults (n= 110) after three months of intensive balance and weight training. Tai Chi significantly improved both strength and balance for six months after the intensive training despite decrements over the intervention period.…”
Section: Strength and Balancementioning
confidence: 99%